Formulasi kombucha teh hijau tayu berbasis variasi jenis gula sebagai pangan fungsional: Analisis sensoris, kadar gula, dan aktivitas antioksidan - Sutyawan Sutyawan; Endah Mayang Sari; Emmy Kardinasari; Karina Dwi Handini (Poltekkes Kemenkes Aceh, 2026)
Background: Green tea and sugar are the main ingredients of kombucha. The antioxidant compounds in kombucha may play a role in the management of glucose metabolism. Using local Tayu green tea and a variety of sugars may potentially achieve the best kombucha characteristics for individuals with diabetes.Objectives: This study aimed to identify the sensory characteristics, total sugar content, and antioxidant activity of tayu green tea kombucha fermented with different sugar types.Methods: A Completely Randomized Design was used in this study. Three treatments based on the type of sugar in Tayu green tea kombucha were used: coconut sugar kombucha (GK), palm sugar kombucha (GA), and cane sugar kombucha (GT). Three kombucha samples were developed in the Pangkalpinang Laboratory and analyzed in the Bogor Laboratory from July to August 2025. The sensory characteristics were described based on product acceptability obtained from a hedonic test involving 30 panelists. The total sugar content was determined using the Luff Schoorl method, and the antioxidant activity was determined using the spectrophotometric method as IC50. Differences in acceptability data were analyzed using the Kruskal–Wallis test (p<0.05). Sugar content and antioxidant activity were analyzed univariately.Results: Significant differences (p<0.05) in color and taste acceptability were observed, with the highest average observed for GK kombucha. The highest aroma and overall acceptability scores were observed for GT (4.3) and GK (4.6) samples. GK kombucha had the lowest IC50 value (6682.9mg/L), indicating the highest antioxidant activity because a lower concentration was required to neutralize 50% of free radicals. GA kombucha had the lowest sugar content at 12.1%, and GK had a slightly higher sugar content at 13.3%.Conclusion: GTK with coconut sugar is the best formula for DM, with the highest acceptability value, moderate sugar content, and highest antioxidant activity.